Defending Farmers' Seed Freedom. Issue 2 (December 2016) - Shiva, Vandana
This article is an eco-feminist approach to understanding sustainability and social change, and engages with issues such as why the homogenization of crop production is dangerous, why it is the multinational corporation seed industry that needs regulations and not the small farmers and how colonization is taking place through seed patents. It also documents the Navdanya movement for the protection of biological and cultural diversity, raises concerns about the ecological and health impacts of genetically modified organisms (GMOs), addresses the issue of farmers' suicide in India after the introduction of Bt cotton in the country, addresses the ongoing fight against the US seed giant Monsanto for the illegal and unauthorized manner in which GMO has been introduced in India, and highlights farmers' rights vis-à-vis the seed.